Childhood Traumatic Experiences and Dissociative Phenomena in Eating Disorders: Level and Association with the Severity of Binge Eating Symptoms. Issue 1 (1st January 2018) - Palmisano, Giovanni L.; Innamorati, Marco; Susca, Giovanna; Traetta, Denise; Sarracino, Diego; Vanderlinden, Johan
ABSTRACT: The aim of the current study is to evaluate the presence of childhood trauma, psychoform, and somatoform dissociation in eating disorders (ED). Eighty-six ED outpatients participated in this study, 20 of them were diagnosed with restrictive anorexia (AN-R), 10 of them with anorexia nervosa binge-purging subtypes (AN-B), 25 with bulimia nervosa (BN), and 31 with binge eating disorder (BED). They were matched by sex and age with a control group consisting of 86 healthy subjects (HC). Traumatic experiences were assessed by means of the Childhood Trauma Questionnaire (CTQ), psychological, and somatoform dissociation, respectively, by means of the Dissociative Experience Scale (DES-II) and Somatoform Dissociation Questionnaire (SDQ-20), and binge eating symptoms by means of Binge Eating Scale (BES). ED subjects showed higher levels of childhood trauma, and both psychoform and somatoform dissociation compared to HC subjects. ED patients showed higher levels of childhood trauma compared to the HC group. No significant differences were shown between ED subgroups with respect to all forms of childhood trauma. BN and AN-B subgroups showed higher levels of both psychological and somatoform dissociation. Dissociation and childhood trauma predicted the severity of binge eating symptoms. Our results confirm previous studies in the same field.